Implementasi Protokol Modbus Tcp Pada Sistem Monitoring Besaran Listrik Menggunakan Labview Dan Power Meter Schneider 810 - Baralangi, Stefany Yunita; Tangdililing, Ferdianto (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2014)
This research aims to develop software applications that can perform data communication from a sensor electrical quantities to the Master Terminal Unit as a server with Modbus TCP protocol. Data communication architecture in real time from the sensor to the MTU so that the user can monitor the amount of electricity in a building at any time. Software applications that are built using tools LabView. The results of data acquisition can be stored in computer memory that will be used as a reference in further analysisKeywords: Modbus TCP, monitoring, Power Meter, LabView